Pengaruh Persepsi Pasien Tentang Mutu Pelayanan terhadap Minat Kunjungan Ulang di Puskesmas Lowu-Lowu - Eky Endriana Amiruddin; Nima Meilani; Muhamad Subhan; Rahmat Rahmat (Jurnal Ilmiah Kesehatan (JIKA), 2021)
In the last three years, there has been a decrease in patient return visits at the Lowu-Lowu Health Center, visit data in 2018 showed a decrease of 35%. The purpose of the study was to determine the effect of patient perceptions of service quality on interest in revisiting the Lowu-Lowu Public Health Center in 2020. The materials and methods used in this study were analytical research with a cross sectional study approach. The population in this study were patients who made repeat visits to the Lowu-Lowu Health Center in 2019 were 768 patients. The sample in this study were 263 patients. The result of this research is that there is an influence between the patient's perception of the quality of health services based on the reliability of the interest in using it again (p = 0.000 < a = 0.05). There is an influence between the patient's perception of the quality of health services based on responsiveness to the interest in reusing the Lowu-Lowu Health Center (p = 0.039 < a = 0.05). There is an influence between the patient's perception of the quality of health services based on health insurance on the interest in reusing the Lowu-Lowu Health Center (p = 0.04 < a = 0.05). There is an influence between the patient's perception of the quality of health services based on physical evidence on the interest in reusing the Lowu-Lowu Health Center (p = 0.004 < a = 0.05).